Neurologic running injuries - McKean, K. A. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
Neurologic running injuries account for a small number of running injuries. This may be caused by misdiagnosis or underdiagnosis. Nerve injuries that have been reported in runners include injuries to the interdigital nerves and the tibial, peroneal, and sural nerves. In this article, the etiology, symptoms, diagnosis, and treatment of these injuries are reviewed. Differences between nerve injury and more common musculoskeletal injury have been presented to aid in differential diagnosis.